FROM CANVAS TO PLATFORM: REFLECTING ON THE DIGITAL PLATFORM CANVAS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: In this article, the canvas used to simplify business modeling of a platform and its visual depiction are put into the entrepreneurial context, and critically reflected accordingly. Furthermore, it is discussed to what extent the canvas is advantageous, disadvantageous, applicable, not applicable, or even contradictory.Methodology: The analysis is based on theoretical research. Additionally, qualitative interviews with business founders were conducted.Results: The results conclude that the canvas employed to ease the business model sharpening process supplies founders with essential aspects to cover, yet they are part of a large set of factors that play in.Conclusion: The limitations of this study are rooted in the chosen research design based on the conceptual review.